EKSISTENSI PENGADILAN PAJAK DALAM LINGKUNGAN PERADILAN TATA USAHA NEGARA - Elfran Bima Muttaqin; Pasolang Pasapan (Paulus Law Journal, 2022)
This study aims to find out and understand how the existence of the tax court in Indonesia and specifically the State Administrative Court. This writing begins with a review of Law No. 14 of 2002 concerning the Tax Court jo. Law Number 28 of 2007 concerning the Third Amendment to Law Number 6 of 1983 concerning General Provisions and Tax Procedures. Results and analysis reveal. The tax court as a special court is part of the exercise of judicial power and is within the State Administrative Court according to Law no. 48 of 2009 in conjunction with Law No. 51 of 2009. The tax court is not really within the State Administrative Court, even though the law has mandated that the tax court is a special court within the State Administrative Court.